Flood and Drought Analysis Of Godavari Sub Basin Based on Precipitation Index - et. al., S. Venkatcharyulu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Godavari river is one of the largest river in the India . Various government agencies are monitoring the hydrological flood and drought studies in the region, the most of the river flowing in the Maharashtra and Terengganu and Andhra prudish , states of India he flood forecasting is based on the precipitation classified . The flood forecasting and drought scenarios like rain fall intensity, depth of run of water and, water levels and spread area over the study area has analyzed. Drought effects in aspect of irrigation has also analyzed over a period of historical data in the Telangana state( India ) and Godavari of sub basin. The aim of this paper is analyzing the flood and drought of study areas based on the intensity of the precipitation from historical data and The result obtained from this analysis is presented in form graphs . The Godavari flood and drought scenarios are very important to analyze the study area to protect the natural disasters and also to take preventive measures for the future floods and droughts. Some data has collected from the Government agencies to obtain the better result. The study area has total 141 number weather stations. Important weather stations where is collected maximum precipitation and least, average precipitation data has used for the analysis. The results available are presented in the form of graphs and numerical evaluation. Study is carried out in the G5, G6, G10 (Godavari sub Basin5, Godavari sub Basin6, Godavari sub Basin10 ) Godavari sub Basin